Bumdesa's Role In Village Poverty Reduction - Suarmanayasa, I Nengah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
BUMDes plays a crucial role in poverty alleviation as a village economic institution. Its establishment was aimed at eradicating poverty, which is a prevalent issue in most Indonesian villages. Villages have the potential for community empowerment, development of infrastructure and services, and poverty alleviation. The objective is to eliminate poverty and minimize the poverty rate. Through descriptive qualitative analysis and data obtained from literature review, scientific studies, and relevant laws and regulations, the researcher is interested in producing a scientific paper on the role of BUMDes in reducing poverty in villages. Conclusion is that when BUMDes are managed professionally and effectively through empowerment, community can participate in becoming village entrepreneurs who produce marketable products in collaboration with BUMDes, thus empowering community and enabling them to meet their basic needs and free them from shackles of poverty that they suffered for so long.